Study of image guided fine needle aspiration cytology in cases of hepatic mass lesions - Dr. Nilima Sawke; Dr. Nipun Madhaw; Dr. G. K. Sawke (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Ultrasound guided Fine needle aspiration cytology (FNAC) has been provedto be a very effective and rapid means of obtaining tissue from liver for pathological evaluation of benign, malignant and inflammatory hepatic lesions. Aims and objectives: The role of Fine needle aspiration cytology as a first line of investigation in space occupying lesions of liver and to study the various cytological patterns in hepatic lesions, categorizing them into non-neoplastic and neoplastic lesions. Materials and Methods: This was a prospective study comprising of 76 cases of liver lesions diagnosed clinically or radiologically. Abdominalultrasonography was carried out in all cases. FNAC was performed under ultrasound guidance. Smears were stained with H & E (Hematoxylene & Eosin) and Wrights stain and were examined for detailed cytomorphological analysis. Results: Among 76 cases included in the study, cases of primary malignancy of liver (Hepatocellular carcinoma) were 45(59%), and metastatic carcinomas were 21(28%). Benign neoplastic lesions were total 4(5%) including hepatic adenoma 3cases and 1case of hemangioma. About 6 (8%) cases were found to be inflammatory lesions of liver. Hepatocellular carcinoma was most common diagnosis followed by liver metastasis of adenocarcinoma. Frequency of hepatic mass lesions was almost equal in both male (39 cases) and female (37 cases) being ratio of 1:1. Conclusion: Guided FNA is a first line of investigation in space occupying lesions of liver as the procedure is safe, simple, rapid, effective and can be employed for pathological evaluation of both malignant and non-malignant hepatic lesions. Malignant tumors were the commonest of the liver lesions with highincidences of primary and metastatic deposits. On radiological examination, neoplastic and nonneoplastic lesions show overlapping features, hence cytomorphological analysis by FNAC increases the diagnostic accuracy.